PEMBELAJARAN INTERAKTIF SEJARAH KEBUDAYAAN ISLAM BERBASIS TEKNOLOGI UNTUK MENINGKATKAN PEMAHAMAN PESERTA DIDIK - Hariyadi, Romdlon; Roqib; Mustaqimah, Raisatul (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) STIT Muhammadiyah Tempurejo, Ngawi, Jawa Timur, 2023)
The teaching of Islamic Cultural History (Sejarah Kebudayaan Islam, SKI) is often perceived as monotonous by students due to traditional instructional methods. Therefore, innovative approaches are needed to enhance learning engagement through interactive, technology-based methods. This article examines the effectiveness of interactive learning in improving students’ understanding of SKI. A qualitative descriptive research method was employed, utilizing literature studies and data analysis from relevant studies. The findings indicate that using interactive media, such as e-learning, animated videos, and gamification, significantly increases students’ motivation and comprehension. Thus, integrating technology into SKI instruction proves to be an effective solution for creating a more engaging and meaningful learning experience.